2007
DOI: 10.2353/jmoldx.2007.060157
|View full text |Cite
|
Sign up to set email alerts
|

CYP1B1 Mutation Profile of Iranian Primary Congenital Glaucoma Patients and Associated Haplotypes

Abstract: The mutation spectrum of CYP1B1 among 104 primary congenital glaucoma patients of the genetically heterogeneous Iranian population was investigated by sequencing. We also determined intragenic single nucleotide polymorphism (SNP) haplotypes associated with the mutations and compared these with haplotypes of other populations. Finally, the frequency distribution of the haplotypes was compared among primary congenital glaucoma patients with and without CYP1B1 mutations and normal controls. Genotype classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 39 publications
4
44
0
Order By: Relevance
“…But, it is found that patients with heterozygous CYP1B1 mutations have a better prognosis after surgery than patients with homozygous/compound heterozygous CYP1B1 mutations (13). Notable sequence heterogeneity is observed in CYP1B1 gene among the Iranian patients with PCG.…”
Section: Discussionmentioning
confidence: 95%
“…But, it is found that patients with heterozygous CYP1B1 mutations have a better prognosis after surgery than patients with homozygous/compound heterozygous CYP1B1 mutations (13). Notable sequence heterogeneity is observed in CYP1B1 gene among the Iranian patients with PCG.…”
Section: Discussionmentioning
confidence: 95%
“…Reports indicate that several CYP1B1 mutations in different societies have been associated with different phenotypes of the disease (mild, moderate, and severe). In the first study conducted in Iran, CYP1B1 mutations were responsible for PCG in 70% (40) and for JOAG in 17.4% (28) of patients but were not responsible for POAG and JOAG in southeastern Iran (41). CYP1B1 mutations show incomplete penetrance in the Iranian population (32).…”
Section: Primary Congenital Glaucomamentioning
confidence: 99%
“…An Iranian PCG patient was identified who harbored the p.Gly61Glu (c.182G>A) mutation in CYP1B1 [8]. He was born to consanguineous parents, had two PCG-affected siblings, and his father was diagnosed with POAG (online suppl.…”
Section: Methodsmentioning
confidence: 99%
“…Presently, two causative genes for PCG are known, CYP1B1 and LTBP2 , which encode, respectively, cytochrome P450 family 1 subfamily B polypeptide 1 and latent transforming growth factor-β binding protein 2 [6,7]. Whereas the four known POAG genes are together estimated to account for the disease status in less than 10% of POAG patients, mutations in CYP1B1 account for PCG in a large fraction of patients [5,8]. They are estimated to be the cause of disease in 70% of Iranian PCG patients [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation